2009
DOI: 10.1002/jrs.2278
|View full text |Cite
|
Sign up to set email alerts
|

A study of collective motions in liquid tert‐butanol from low‐wavenumber Raman scattering

Abstract: The collective properties of liquid tert-butyl alcohol (TBA) were analysed by low-wavenumber Raman (LWR) scattering spectroscopy. Vibrational and relaxation phenomena of this H-bonding system were assessed in pure liquid phase at different temperatures in the 15-70 • C range, and in solution with 2,2 -dimethyl butane (2,2 -DMB) and water as a function of composition in the 0.7 ≤ x TBA ≤ 0.9 range at constant temperature (T = 25 • C). The LWR spectrum of pure TBA (below 150 cm −1 ) was expressed by the dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The Raman spectra of TBA solutions (which contain data analogous to the Im [D 0 (o)]) have been reported before by Tominaga et al 72 and Sassi et al, 16 although their data were collected at relatively high concentrations (>2.3 M 72 and >9.5 M 16 ). Tominaga et al 72 showed that the spectra of TBA-water solutions could be decomposed into linear combinations of water and neat TBA spectra in the frequency range 80-400 cm À1 .…”
Section: Concentration Dependencementioning
confidence: 68%
See 2 more Smart Citations
“…The Raman spectra of TBA solutions (which contain data analogous to the Im [D 0 (o)]) have been reported before by Tominaga et al 72 and Sassi et al, 16 although their data were collected at relatively high concentrations (>2.3 M 72 and >9.5 M 16 ). Tominaga et al 72 showed that the spectra of TBA-water solutions could be decomposed into linear combinations of water and neat TBA spectra in the frequency range 80-400 cm À1 .…”
Section: Concentration Dependencementioning
confidence: 68%
“…Tominaga et al 72 showed that the spectra of TBA-water solutions could be decomposed into linear combinations of water and neat TBA spectra in the frequency range 80-400 cm À1 . Sassi et al 16 reported that the spectral evolution observed by varying the concentration from pure TBA down to 9.5 M was similar to the effect produced by lowering the temperature of neat TBA. The Im [D 0 (o)] obtained from OHD-OKE measurements are shown in Fig.…”
Section: Concentration Dependencementioning
confidence: 85%
See 1 more Smart Citation
“…The asymmetric band at ca. 50 cm −1 is typical of many hydrogen-bonding liquids, 60 including aliphatic alcohols 61 , 62 and is generally ascribed to librational motions of the solute molecules. 61 Here, the comparison with the spectrum of pure TBA (Figure 7) confirms this assignment.…”
Section: Resultsmentioning
confidence: 99%
“…Dong et al [250] used spatially resolved Raman scattering together with in situ microscopy to study mixed Na 2 SO 4 /MgSO 4 aerosol particles with molar ratios of 1 : 1 and 2 : 1 deposited on a quartz substrate to gain a better understanding of their evaporation processes. Sassi et al [251] used low-frequency Raman scattering to study the collective motions in liquid tert-butanol. Vibrational and relaxation phenomena of this H-bonding system were assessed in pure liquid phase at different temperatures and in solution with 2,2-dimethylbutane and water as a function of composition.…”
Section: Other Liquid and Solution Studiesmentioning
confidence: 99%